Demographic characteristics and spectrum of comorbidities in patients with muscle tension dysphonia: a retrospective cross-sectional study - Sotirović, Jelena; Petrović, Maša; Milojević, Milanko; Baletić, Nenad; Čukić, Ognjen; Zaletel, Ivan (Vojnosanitetski pregled, 2025)
Background/Aim. Muscle tension dysphonia (MTD) is one of the most common voice disorders. The aim of the study was to examine demographic characteristics and the prevalence of comorbidities in patients diagnosed with MTD. Methods. A retrospective cross-sectional study included an analysis of demographic characteristics and comorbidities in 87 patients diagnosed with MTD during a one-year period. Results. The mean age of the patients was 49.2 years (range 18–84 years), and 79.3% were younger than 65 years. The female gender comprised 73.6%. No statistically significant difference was found in smoking status between men and women (χ2 = 0.624; p ˃ 0.05). Out of the 87 patients, 43 (49.4%) were professional voice users. Among these patients, 20 (46.5%) were school teachers, 8 (18.6%) sales-related occupations, 5 (11.6%) professional singers, 3 (7.0%) kindergarten teachers, 3 (7.0%) lecturers, 2 (4.6%) psychologists, 1 (2.3%) speech-language pathologist, and 1 (2.3%) fitness instructor. Secondary MTD was diagnosed in 36 (41.4%) patients. The most common clinical findings diagnosed in those with secondary MTD were vocal cord nodules in 24 patients (66.7%). The prevalence of comorbidities were as follows: mild to moderate hearing loss (9.2%), postnasal drip (31.0%), hypersensitivity to common inhalant allergens (31.0%), asthma or chronic obstructive pulmonary disease (18.4%), thyroid dysfunction (17.2%), and history of gastroesophageal reflux disease (21.8%). Conclusion. MTD is more frequent in females and professional voice users. Due to the high prevalence of comorbidities in MTD patients, a detailed history and additional examinations are necessary in order to determine the final treatment plan.